Functional impairment assessed by the Barthel Index influenced outcomes after transcatheter aortic valve implantation. (2nd January 2020) - El Garhy, Mohammad; Owais, Tamer; Abdulrahman, Mohamed; Schreiber, Torsten; Schulze, Christian; Lauer, Bernward; Kuntze, Thomas
Abstract: Objective. We investigated the influence of functional impairment assessed by the Barthel index (BI) on the three-month outcomes after transfemoral-transcatheter aortic valve intervention (TF-TAVI) under general anesthesia. Design . We included retrospectively analyzed 336 patients undergoing TAVI between January 2017 and January 2018 in central hospital, Bad Berka, Germany. All patients were followed up at three-month in our center's outpatient clinic. We stratified the patients according to the BI. Results . At baseline, 76 patients had a BI <80. Patients with a BI <80 were characterized by advanced age (80.6 ± 5.6 vs. 83 ± 4.1 years. p = .027), diabetes mellitus on insulin and higher surgical risk scores. A prior cerebral ischemic event was recorded more in patients with a BI ≥80. Regarding intermediate outcomes, three-month mortality was significantly higher in patients with a BI <80. Patients with a BI <80 developed significantly more postoperative cardiac decompensation, delirium and strokes. Patients with BI <80 had lower hemoglobin level preoperative and needed more blood transfusion postoperative. Other valve academic research consortiums (VARCs) complications were equally distributed in both groups. A BI <80 was associated with prolonged postoperative hospital stay and was an independent predictor of FT protocol failure (OR 4; CI 95% 1.3–11. p .02). Conclusions . A BI <80 is associated with increased mortality and risk of neurological events and cardiac decompensations after TF TAVI. A BI <80 is an independent predictor of failure in fast track TAVI.